2021
DOI: 10.3389/fvets.2021.640751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waiting Room and Feline Facial Pheromone Experience on Blood Pressure in Cats

Abstract: Obtaining accurate blood pressure measurements in cats is challenging due to the stressful nature of clinic visits. The objective of this study was to evaluate the effects of veterinary clinic waiting experiences and a feline pheromone spray on blood pressure in the cat. We hypothesized that reduced stress associated with bypassing the waiting room and use of synthetic feline facial pheromone (FFP) spray would result in lower blood pressure. A 2 × 2 factorial design involved two rooms and two FFP treatments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…17 The effect of feline facial pheromone analogues on feline stress and blood pressure remains unclear, as studies have shown improvement of stress behavior that is not reflected in physiologic parameter changes, such as systolic blood pressure, with the use of these pheromones. 19,20 In our survey, two-thirds of the veterinarians who employed techniques to reduce situational hypertension reported using feline pheromones; however, only a minority (9%) perceived this technique as most helpful. A study showed that owners taking blood pressure measurements with the HDO device without a veterinarian did not impact blood pressure measurements; however, cats placed on a table rather than a carrier were shown to have higher mean arterial pressure, diastolic pressure and pulse rate.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…17 The effect of feline facial pheromone analogues on feline stress and blood pressure remains unclear, as studies have shown improvement of stress behavior that is not reflected in physiologic parameter changes, such as systolic blood pressure, with the use of these pheromones. 19,20 In our survey, two-thirds of the veterinarians who employed techniques to reduce situational hypertension reported using feline pheromones; however, only a minority (9%) perceived this technique as most helpful. A study showed that owners taking blood pressure measurements with the HDO device without a veterinarian did not impact blood pressure measurements; however, cats placed on a table rather than a carrier were shown to have higher mean arterial pressure, diastolic pressure and pulse rate.…”
Section: Discussionmentioning
confidence: 85%
“…1218 Studies have evaluated the efficacy of only a select number of methods to reduce false increases in NIBP measurements in conscious cats, including management of the clinical setting, acclimation to the environment and the use of feline facial pheromone analogues. 4,17,1921 In general, the optimal approach to NIBP measurement in conscious cats remains controversial and the preferences of practicing veterinarians on this subject are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2020, Van Vertloo et al . 2021). Finally, the cage environment should ideally provide comfort, space and opportunities for movement and possibility to retreat or hide.…”
Section: Sectionmentioning
confidence: 99%
“…6,7 In addition, studies have evaluated the efficacy of some methods to reduce falsely high BP readings in conscious cats and found variable responses. [9][10][11][12][13][14] Several effective approaches have been identified, including allowing time for cats to acclimate to the environment 9 and placing cats in their own carrier during measurement. 10 Veterinarians commonly obtain non-invasive BP measurements in cats using a Doppler ultrasonic flow detector.…”
Section: Introductionmentioning
confidence: 99%